Khazanah theologia - UIN Sunan Gunung Djati. Program Pascasarjana (Pascasarjana, UIN Sunan Gunung Djati Bandung, 2019)
Religious Studies, theology, and related fields and particularly focuses on the metatheoretical conception of the relation between theology and theory of religion.
Keywords: Religion : Periodicals; Religion